Measurement of the Thickness of Submental Muscles by Ultrasonography in Healthy Children - Uysal, Emine; Öztürk, Mehmet; Bayramoğlu, Zuhal; Yasir Özlü, Mustafa; Erdur, Ömer (ENT Updates, 2021)
Background: Submental muscles are vital for swallowing as they are responsible for hyolaryngeal elevation. This study aimed to determine the normative values of submental muscles in healthy children. Methods: The thickness of the digastric muscle, the thickness of the mylohyoid muscle, and the thickness of the geniohyoid muscle were measured in 218 (124 boys and 94 girls) healthy children by the ultrasonography. Correlation analysis of the thickness of the digastric muscle, the thickness of the mylohyoid muscle, and the thickness of the geniohyoid muscle with gender, age, height, weight, and body mass index were performed, and median values were determined in preschool, school, and adolescent age groups. Results: No significant differences were found in median height, weight, body mass index, the thickness of the digastric muscle, the thickness of the mylohyoid muscle, and the thickness of the geniohyoid muscle values of the males and females (P > .05). There were highly significant mild to moderate positive correlations of age, height, weight, and body mass index with the thickness of the digastric muscle, the thickness of the mylohyoid muscle, and the thickness of the geniohyoid muscle parameters (P = .001, r = 0.26-0.58). The thickness of the digastric muscle was 4.3 mm, 4.5 mm, and 5.4 mm in the preschool, school, and adolescent groups, respectively. In the preschool, school, and adolescent groups, the thickness of the geniohyoid muscle was 4.8 mm, 5.35 mm, and 6.25 mm, respectively. The thickness of the mylohyoid muscle was found as 1.6 mm, 1.9 mm, and 2.3 mm in preschool, school, and adolescent groups, respectively. Conclusion: Submental muscles that perform hyolaryngeal elevation can be easily evaluated with the ultrasonography. Knowing the normative thickness values of submental muscles according to age groups in children will contribute to the diagnosis of atrophy or hypertrophy in these muscles. It can also be used in the follow-up of dysphagia treatment.